Extractive relations : countervailing power and the global mining industry - Owen, John R. (Routledge, an imprint of the Taylor & Francis Group, 2017)
"Extractive Relations explores the nature of industrial power and its role in shaping what we understand to be the global mining sector. The authors examine issues at the forefront of contemporary debates: corporate obligations in safeguarding the rights of people displaced by mining, the recognition of community rights and interests in supporting or opposing mining developments, the handling of non-judicial grievances and work-ability of corporate remedy systems, and the logic of community relations departments in navigating these issues inside and outside of the typical modern mining establishment.The authors develop a unique theoretical approach that highlights the different types and uses of power in these settings. This perspective is supported by the authors' own sustained engagement with the mining sector over many years, drawing on cases from over twenty countries. The analysis of these issues from both 'inside' and 'outside' the sector is a key point of differentiation. For readers seeking to understand how mining companies interpret and interact with the communities and interests around their operations, this book provides invaluable insight and analysis."--Provided by publisher.